PENINGKATAN CD8 DAN IFN-Î³ PADA HYPERSENSITIVITY PNEUMONITIS (HP) AKIBAT PAJANAN DEBU PENGGILINGAN PADI (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Abstrak Masalah klinis kesehatan kerja pada pekerja penggilingan padi saat ini adalah penyakit saluran pernafasan. Penelitian ini bertujuan untuk menganalisis peningkatan CD8 dan IFN-Î³ pada Pneumonitis Hipersensitif (HP) akibat pajanan debu penggilingan padi pada mencit (Musmusculus) BALB/C. Penelitian yang dilakukan adalah penelitian eksperimental laboratoris dengan hewan coba mencit (Musmusculus) BALB/C, rancangan penelitian yang digunakan adalah Randomized the post test only control group design. Mencit (Musmusculus) BALB/C dipajan dengan debu penggilingan padi selama empat jam/hari selama tiga puluh hari dengan konsentrasi 0.50 mg/m3, 0.75 mg/m3, 1.00 mg/m3. Variabel bebas adalah debu penggilingan padi, sedangkan variabel tergantung adalah CD8 dan IFN-Î³, serta gambaran histopatologis paru mencit, sedangkan variabel kendali adalah strain, berat badan, dan umur. Hasil penelitian menunjukkan bahwa terjadi peningkatan kadar CD8 antara kontrol dengan perlakuan, dan secara statistik ada perbedaan yang bermakna. Kemudian terjadi peningkatan IFN-Î³ dan secara statistik ada perbedaan yang bermakna antara kontrol dan perlakuan pada mencit (Musmusculus) BALB/C. Hasil penelitian dapat digunakan sebagai dasar upaya pencegahan dan pemberian terapi penyakit HP lebih dini sehingga dapat meningkatkan kualitas paru. Kata Kunci: CD8, IFN-Î³, debu penggilingan padi Abtract The purpose of this research was to analyze increase of CD8 and IFN-Î³ of Hypersensitivity Pneumonitis (HP) as a result from the exposure of dust from paddy milling on mice (Musmusculus)BALB/C. The research done was a laboratory experimental research with mice (MusMusculus) as experimental animal. The research design used was the post only control group design using mice (MusMusculus) Balb/c as experimental animal. Mice (Musmusculus) Balb/c were exposed to dust from paddy milling for four (4) hours/day and it was done for thirty (30) days with the exposed concentrations respectively were 0.50 mg/m3, 0.75 mg/m3, 1.00 mg/m3.The research variables were free variable, dependent variable, and control variable. Independent variable was dust from paddy milling, dependent variables were Hypersensitivity Pneumonitis (HP), CD8 and IFN-Î³, while control variables were strain, body weight and age of mice (MusMusculus) Balb/c. The research result showed that there was an increase of CD8, and statistically there was significant difference; there was an increase on IFN-Î³ and statistically there was a significant difference between the study and control on mice BALB/C. It was suggested that: the research result be used to underlie a preventive action and an early therapy on Hypersensitivity Pneumonitis (HP) so that it increase the quality of lung. Keywords: CD8, IFN-Î³, dust from paddy milling Abtract The purpose of this research was to analyze increase of CD8 and IFN-Î³ of Hypersensitivity Pneumonitis (HP) as a result from the exposure of dust from paddy milling on mice (Musmusculus)BALB/C. The research done was a laboratory experimental research with mice (MusMusculus) as experimental animal. The research design used was the post only control group design using mice (MusMusculus) Balb/c as experimental animal. Mice (Musmusculus) Balb/c were exposed to dust from paddy milling for four (4) hours/day and it was done for thirty (30) days with the exposed concentrations respectively were 0.50 mg/m3, 0.75 mg/m3, 1.00 mg/m3.The research variables were free variable, dependent variable, and control variable. Independent variable was dust from paddy milling, dependent variables were Hypersensitivity Pneumonitis (HP), CD8 and IFN-Î³, while control variables were strain, body weight and age of mice (MusMusculus) Balb/c. The research result showed that there was an increase of CD8, and statistically there was significant difference; there was an increase on IFN-Î³ and statistically there was a significant difference between the study and control on mice BALB/C. It was suggested that: the research result be used to underlie a preventive action and an early therapy on Hypersensitivity Pneumonitis (HP) so that it increase the quality of lung. Keywords: CD8, IFN-Î³, dust from paddy milling